Improve Student Effectiveness And Efficiency In Reading With Ability Using Scramble Technique At Sd Negeri 08 Pasar Surantih - Afridawanti Afridawanti (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. Problems to be studied in this research are: a. How to improve the results of student achievement class I SD Negeri 08 Surantih Market by using scramble technique in January 2016? b. Steps taken in improving the learning outcomes of Bahasa Indonesia? This research was conducted in class I SDN 08 Pasar Surantih In January 2016. Schools whose inhabitants are mostly self-employed livelihoods. The determination of this location is based on the fact that the school has never been a researcher doing Classroom Action Research (PTK), and student achievement in this school is still relatively low compared to other schools. Choose class I as respondent with reason: (a) cognitive development level 8-10 years already have ability. (b) the existence of variations of students, judging by the social status, education and work of their parents (c) the problems faced by the first grade students in reading. The focus of attention in this research is to improve the ability to read through sceramble techniques in grade I students. Besides, it will also see the interest and motivation of students in reading on Indonesian language subjects in elementary school (SD). From the results of learning activities that have been conducted for three cycles, and based on all the discussion and analysis that has been done can be summed up as follows: 1. Learning with cooperative concept teaching model scramble has a positive impact in improving student achievement marked by the improvement of student learning mastery in each cycle, that is cycle I (62,50%), cycle II (75,00%), cycle III (87,50%). 2. Implementation of cooperative concept teaching model of scramble have positive influence, that is can improve student's learning motivation to learn indonesian language lesson which is indicated by mean of student answer which states that student interested and interested with teaching model of scramble so that they become motivated to learn.